A structure-based design approach to advance the allyltyrosine-based series of HIV integrase inhibitors. Issue 12 (22nd March 2018) - Gordon, Christopher P.; Dalton, Neal; Vandegraaff, Nicholas; Deadman, John; Rhodes, David I.; Coates, Jonathan A.; Pyne, Stephen G.; Griffith, Renate; Bremner, John B.; Keller, Paul A.
Abstract: As of mid-2017, only one structure of the human immunodeficiency virus (HIV) integrase core domain co-crystallised with an active site inhibitor was reported. In this structure (1QS4), integrase is complexed with a diketo-acid based strand-transfer inhibitor (INSTI). This structure has been a preferred platform for the structure-based design of INSTIs despite concerns relating to structural irregularities arising from crystallographic packing effects. A survey of the current pool of 297 reported integrase catalytic core structures indicated that the anatomy of the active site in the complex structure 1QS4 exhibits subtle variations relative to all other structures examined. Consequently, the 1QS4 structure was employed for docking studies. From the docking of twenty-seven allyltyrosine analogues, a 3-point inhibitor binding motif required for activity was established and successfully utilised in the development of a tripeptide displaying an EC50 value of 10 ± 5 μM in HIV infected human T-cells. Additional docking of "in-house" compound libraries unearthed a methyl ester based nitrile derivative displaying an IC50 value of 0.5 μM in a combined 3′-processing and strand-transfer assay. Graphical abstract: